HUBUNGAN POLA ASUH DAN KECERDASAN SPIRITUAL TERHADAP KONTROL DIRI SISWA SMP NEGERI DI KECAMATAN PAGERUYUNG (IMPLIKASI DALAM BIMBINGAN DAN KONSELING) - Aulia, Safira Rahma; Utomo, Dian Purbo (IKIP Siliwangi, 2026)
This study focuses on examining the relationship between parenting styles and spiritual intelligence on self-control possessed by junior high school students in Pageruyung District. The method used in this study is quantitative correlation with data collection techniques using parenting style scales, spiritual intelligence scales, and self-control scales with a Likert model. The total population was 759 students and a sample of 262 students spread across grades VII, VIII, and IX at junior high schools in Pageruyung District obtained through probability sampling techniques with proportionate stratified random sampling techniques. Data analysis used multiple linear regression. The research findings show that parenting styles and spiritual intelligence simultaneously have a positive and significant relationship with students' self-control by 32.1%, meaning that an increase in the quality of parenting styles and spiritual intelligence is followed by an increase in students' self-control. Meanwhile, the other 67.9% is influenced by other factors outside the research variables. The findings of this study can be used to develop guidance and counseling services that focus on improving students' self-control through strengthening spiritual intelligence and optimizing the role of parental parenting styles.